2023
DOI: 10.1002/chem.202300598
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Room‐Temperature Synergetic Response of Magnetism, Dielectricity and Luminescence Based on (C5NH13Cl)2MnBr4

Abstract: Multifunctional materials with working temperatures near room temperature are crucial for practical applications. Until now, it is still a great challenge to obtain such materials. In this paper, a complex of (C 5 NH 13 Cl) 2 MnBr 4 (1) with a structural phase transition near room temperature is reported. The phase transition induces switchable magnetic properties, dielectric anomalies and luminescent response over the same range of temperatures. It is the first time the synergetic effect of magnetism, dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Since it occurs in the paramagnetic region, it can not be attributed to the magnetic phase transition. Instead, it should be associated with the ferroelectric structural phase transition, which can also affect the magnetic susceptibilities subtly 14,27 .…”
Section: Characterization Of Magnetostrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it occurs in the paramagnetic region, it can not be attributed to the magnetic phase transition. Instead, it should be associated with the ferroelectric structural phase transition, which can also affect the magnetic susceptibilities subtly 14,27 .…”
Section: Characterization Of Magnetostrictionmentioning
confidence: 99%
“…These molecular materials can possess the advantages of both organic and inorganic species within a single phase 19,20 . Moreover, they can be readily modified and optimized by manipulating their specific functional groups 14,21,22 . However, it is important to acknowledge the limitations of molecular ferroelectric and ferromagnetic materials.…”
mentioning
confidence: 99%
“…31 Recently, our group reported a (C 5 NH 13 Cl) 2 MnBr 4 compound showing magnetic, dielectric and luminescence synergistic response near room temperature. 32 Therefore, choosing the right metal ions and ammonium cations to construct OIH materials will greatly improve the chances of assembling multifunctional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other transition metal ions Zn 2+ and Cu 2+ , Mn-based organic–inorganic hybrid halides not only have the advantage of low raw material cost but also exhibit a unique tunable luminescent color, making them an emerging material with fascinating optical, electronic, mechanical, and other properties. By selecting appropriate organic and inorganic components, three-dimensional (3D), two-dimensional (2D), one-dimensional (1D), and zero-dimensional (0D) structures can be obtained. Compared to high-dimensional materials, low-dimensional (0D/1D) hybrids have a higher exciton binding energy and generation energy, thus exhibiting excellent luminescence efficiency and stability. Generally, tetrahedral-coordinated Mn 2+ emits green light, while octahedral-coordinated Mn 2+ emits red light. , As an example, Chen et al reported that the 0D Mn-based hybrid (PPh 4 ) 2 MnBr 4 displays efficient green emission and successfully prepared organic light-emitting diodes, indicating outstanding electroluminescent properties of the material . Xiong et al prepared a series of 1D Mn-based perovskite materials with octahedral geometry and strong red emission. In addition, Ma et al reported an efficient X-ray scintillator of the 0D hybrid (C 38 H 34 P 2 )­MnBr 4 , with a green emission peak of 517 nm and PLQYs of 95% .…”
Section: Introductionmentioning
confidence: 99%